AL'AFEAL ALMAZIDAT FI ALJUZ' AL'AWAL MIN KITAB AL'AKHLAQ LILBANIN LIEUMAR BIN 'AHMAD BIARJA': DIRASAT TAHLILIAT SARFIA - Khairudin; Afianti nur, Andi; Syamsuri, Sholeh (Program Studi Pendidikan Bahasa Arab, 2023)
More verbs are widely used in preparing books and theses. This is because adding letters to the verb will definitely affect the meaning in the sentence. And adding one or two or more letters to the verb would of course have a different meaning. The purpose of this research is to identify the types of verbs that are more and the meanings of their weights in the first part of the Book of Ethics for Boys. The method used by the researcher in collecting materials is the descriptive method, in which data is collected by reading, translating, quoting, and selecting the necessary data, especially what is related to doing more in the first part of the Book of Ethics for Boys. The results of this scientific research indicate that the verbs added in the first part of the Book of Ethics for Boys are three hundred and ninety-six (396) verbs from the weights of the triple verbs added by one letter, two letters, and three letters. And do, and react, and do. And from the weight of the quadruple verb, more comes to the weight of the verb. The researcher discovered that the meanings of the weights of the more verbs in this book are transgression, becoming, diligence, request, participation, in the sense of the abstract trio, affirmation, repetition, obedience, exaggeration, loyalty, multiplying or abundance, affectation, gratitude, comparison, necessity, entitlement, And show